Literature Study on The Application of Blended Learning In Biology Subjects In Schools - Oktavia Oktavia; Riska Maulidya; Zulham Tri Setyo; Eko Sri Wahyuni (Universitas Veteran Bangun Nusantara Sukoharjo, 2023)
This study aims to reveal the effectiveness of Blended Learning as an online and mixed learning strategy by analyzing various research studies related to Blended Learning obtained from the Google Scholar database. The method used in this study is a method with a library approach or what is known as a literature study from research articles for 2020-2022. Article selection is carried out through the process of identification, screening, and eligibility. So that 10 articles are relevant to the objectives and problems of the literature study. Based on the literature study that has been carried out, the results show that the use of Blended Learning by utilizing several digital technology-based applications as learning support can be said to be effective for increasing literacy skills, critical skills, problem-solving abilities, and cognitive learning outcomes of students.